Parasite Fauna Of 3 Species Of Antarctic Whales With Reference To Their Use As Potential Stock Indicators - Dailey, Murray D.; Vogelbein, Wolfgang K. (W&M ScholarWorks, 1991)
Seventeen species of parasites representing the Cestoda, Nematoda, Acanthocephala, and Crustacea are reported from three species of Antarctic whales. Thirty-five sei whales Balaenoptera borealis, 106 minke whales B. acutorostrata, and 35 sperm whales Physeter catodon were examined from latitudes 30-degrees to 64-degrees-S, and between longitudes 106-degrees-E to 108-degrees-W, during the months of November to March 1976-77. Collection localities and regional helminth fauna diversity are plotted on distribution maps. Antarctic host-parasite records from B. borealis, B. acutorostrata, and P. catodon are updated and tabulated by commercial whaling sectors. The use of acanthocephalan parasites of the genus Corynosoma as potential Antarctic sperm whale stock indicators is discussed.